Peningkatan pemahaman konsep matematis pada materi pecahan dengan menggunakan model Course Review Horay (CRH) berbantuan media puzzle pada Siswa Kelas IV SD - Yesika Alfiani; Nur Fajrie; Erik Aditia Ismaya (COLLASE (Creative of Learning Students Elementary Education), 2023)
The understanding of the concepts of students at SD N 1 Bakalan Krapyak is still lacking because mathematics learning activities are still centered on the teacher, namely still using conventional learning methods, teachers do not use media, and students tend to be passive. This study aims to describe the increase in the ability to understand mathematical concepts by using the Course Review Horay learning model on fraction material for fourth grade students of SD 1 Bakalan Krapyak Kudus. This research is a classroom action research using the Kemmis and Mc Taggart model. This research lasted for 2 cycles, each cycle consists of 4 stages, namely, planning, implementation, observation and reflection. The data collection technique used two techniques, namely the test technique using the concept understanding test instrument and the non-test using the observation instrument, interview instrument and documentation. The data analysis used is quantitative and qualitative data analysis. The results showed that the ability to understand mathematical concepts of fourth grade students of SD 1 Bakalan Krapyak Kudus had increased after the Course Review Horay learning model was applied with the help of puzzle media on fractional material. In the first cycle, the class average was 71.07 with a classical completeness percentage of 72, 73% with good criteria. While in the second cycle, the class average score was 75.29 with a classical completeness percentage of 81.82% with good criteria and had reached the KKM score.